- Efetue :
a) (+8x) - (-3x)
b) (-5x) - (11x)
c) (-6y) - (-4y)
d) (+7y) - (+7y)
e) (-3x) - (+4x) + (-3x)
f) (-9x) - (-x)
g) (+2y) -(+5y)
h) (-3m) - (-m)
Soluções para a tarefa
Respondido por
8
a) (+8x) - (-3x) = 8x + 3x ==> 11x
b) (-5x) - (11x) = -5x-11x ==> - 16x
c) (-6y) - (-4y) = -6y + 4y ==> - 2y
d) (+7y) - (+7y) = 7y - 7y = 0
e) (-3x) - (+4x) + (-3x) = -3x-4x-3x ==> - 10x
f) (-9x) - (-x) = -9x + x ==> - 8x
g) (+2y) -(+5y) = 2y - 5y ==> - 3y
h) (-3m) - (-m) = -3m + m ==> - 2m
Respondido por
9
a) (+8x) - (-3x)
+8x + 3x = 11x
b) (-5x) - (11x)
-5x - 11x = -16x (sinais iguais soma)
c) (-6y) - (-4y)
-6y + 4y = -2y (sinais diferentes soma e conserva sinal de número maior)
d) (+7y) - (+7y)
+7y - 7y = 0
e) (-3x) - (+4x) + (-3x)
-3x - 4x - 3x= -10x
f) (-9x) - (-x)
-9x + x = 8x
g) (+2y) - (+5y)
+ 2y - 5y = - 3y
h) (-3m) - (-m)
-3m +m = -2m
+8x + 3x = 11x
b) (-5x) - (11x)
-5x - 11x = -16x (sinais iguais soma)
c) (-6y) - (-4y)
-6y + 4y = -2y (sinais diferentes soma e conserva sinal de número maior)
d) (+7y) - (+7y)
+7y - 7y = 0
e) (-3x) - (+4x) + (-3x)
-3x - 4x - 3x= -10x
f) (-9x) - (-x)
-9x + x = 8x
g) (+2y) - (+5y)
+ 2y - 5y = - 3y
h) (-3m) - (-m)
-3m +m = -2m
Perguntas interessantes